Immunomodulation and Regenerative Capacity of MSCs for Long-COVID - Xin Ya Loke (MDPI AG, 2021)
The rapid mutation of the SARS-CoV-2 virus is now a major concern with no effective drugs and treatments. The severity of the disease is linked to the induction of a cytokine storm that promotes extensive inflammation in the lung, leading to many acute lung injuries, pulmonary edema, and eventually death. Mesenchymal stem cells (MSCs) might prove to be a treatment option as they have immunomodulation and regenerative properties. Clinical trials utilizing MSCs in treating acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) have provided a basis in treating post-COVID-19 patients. In this review, we discussed the effects of MSCs as an immunomodulator to reduce the severity and death in patients with COVID-19, including the usage of MSCs as an alternative regenerative therapy in post-COVID-19 patients. This review also includes the current clinical trials in utilizing MSCs and their potential future utilization for long-COVID treatments.